Integrated Electrocoagulation and Tight Ultrafiltration Membrane for Wastewater Reclamation and Reuse - F.A. Nugroho; Putu Teta Prihartini Aryanti; B. Irawan; M.F. Kurnia; T. Prasetyo (Dept. of Chemical Engineering, Diponegoro University, 2018)
Wastewater reclamation and reuse have become an alternative to saving operational costs while reducing the impact of waste pollution. In this paper, integration of electrocoagulation (EC) and polysulfone-based ultrafiltration (UF-PSf) membranes were used for the mentioned purpose. The EC unit equipped with 7 (seven) pieces of E-shaped of Al electrodes, which operated at a current of 3 (three) Amperes and a residence time of 2 (two) hours. The waste samples obtained from textile and oil palm industries. The experimental results were compared based on product quality and economic feasibility. When used for textile waste treatment, the integrated EC-UF units reduced TDS, TSS, BOD, and COD by 77%, 95%, 70 -80%, and 60-70%, respectively. While in palm oil waste treatment, the TDS and TSS reduced by 92% and 98%. The electrode loss rate in palm oil waste treatment was 2 (two) times greater than textile waste. By assuming that the waste production capacity of both industries was 400 m3/day, the water production cost in textile waste treatment was Rp. 4,000/m3. While in the palm oil waste treatment, the water production cost was Rp. 6,000/m3. These results showed that the EC-UF unit could be used as an economical and environmentally friendly alternative process for reclamation of industrial wastewater that meets the clean water quality standards.Keywords: electrocoagulation, industrial wastewater, ultrafiltration, reclamation, reuse water